The exploitation of FRET probes to track bromodomain/histone interactions in cells for bromodomain inhibitors. (March 2016) - Sasaki, Kazuki; Yoshida, Minoru
Abstract : Bromodomain-containing proteins are epigenetic readers of histone codes, which recognize acetylated histones and are involved in transcription, nucleosome remodeling and DNA repair. Chromosomal translocations of bromodomain-containing proteins have been implicated in many diseases. In this regard, small molecules that inhibit bromodomains are promising as therapeutic agents. A fluorescence microscopy-based approach provides information on bromodomain inhibitors that abrogate the interaction between acetylated histones and bromodomains in living cells. We have developed genetically encoded fluorescent probes for histone acetylation called Histacs. We review how these recently developed probes can serve as useful tools to evaluate the intracellular activity of bromodomain inhibitors.